A novel strategy to purify conductive polymer particles. Issue 9 (8th February 2019) - Spence, Daron; Polizos, Georgios; Joshi, Pooran; Sharma, Jaswinder
Abstract : A novel strategy to purify conductive polymer nanoparticles is presented. Abstract : The purification of conductive polymer ( e.g., polyaniline) particles is a challenging task, especially when the particle size is small. Herein, we demonstrate a unique strategy (electrode-based) to purify polyaniline particles by exploiting the difference in surface charge between particles and surfactants, and compare the results with a commonly used purification strategy (washing).